Granulomatous reaction to hyaluronic acid dermal filler: clinical and histological features - Agosti, Vittorio; Stefanini, Giorgia (Aesthetic Medicine, 2024)
The use of Dermal filler is greatly increased in the past years, indeed now it is one of the most frequent non-surgical cosmetic procedures performed all over the world. Because of its safety profile, hyaluronic acid is the most used injection substance. Although the use of hyaluronic acid in aesthetic medicine is safe, as any other medical procedure it has its own risk to develop complications and adverse effects. The aim of this article it’s to focus on one of them, the granulomatous foreign body reaction. In this mini-review are summarized clinical and histological features of granulomatous foreign body reaction in hyaluronic acid filler.